Water accounting under climate change in the transboundary Volta River Basin with a spatially calibrated hydrological model - Dembélé, Moctar; Salvadore, E.; Zwart, Sander J.; Ceperley, N.; Mariethoz, G.; Schaefli, B. (Elsevier, 2023)
Sustainable water management requires evidence-based information on the current and future states of water resources. This study presents a comprehensive modelling framework that integrates the fully distributed mesoscale Hydrologic Model (mHM) and climate change scenarios with the Water Accounting Plus (WA+) tool to anticipate future water resource challenges and provide mitigation measures in the transboundary Volta River basin (VRB) in West Africa. The mHM model is forced with a large ensemble of climate change projection data from CORDEX-Africa. Outputs from mHM are used as inputs to the WA+ framework to report on water flows and consumption over the historical baseline period 1991–2020 and the near-term future 2021–2050 at the basin scale, and also across spatial domains including four climatic zones, four sub-basins and six riparian countries. The long-term multi-model ensemble mean of the net inflow to the basin is found to be 419 km3 /year with an inter-annual variability of 11% and is projected to slightly increase in the near-term future (2021–2050). However, evaporation consumes most of the net inflow, with only 8% remaining as runoff. About 4 km3 /year of water is currently used for man-made activities. Only 45% of the available water is beneficially consumed, with the agricultural sector representing 34% of the beneficial water consumption. Water availability is projected to increase in the future due to the increase in rainfall, along with higher inter-model and inter-annual variabilities, thereby highlighting the need for adaptation strategies. These findings and the proposed climate-resilient land and water management strategies can help optimize the water-energy-food-ecosystem nexus and support evidence-based decisions and policy-making for sustainable water management in the VRB.